Obstetrical and perinatal consequences of childbirth in women with antenatally undiagnosed fetal growth restriction - Puchkov, V. A.; Pavliuchenko, M. I.; Bohomolova, O. A. (Modern medical technology, 2023)
Fetal growth restriction (FGR) is one of the most studied topics in the medicine of the mother and fetus. However, not identified antenatally FGR can have an increased risk of both perinatal morbidity and mortality, as well as adverse long-term consequences. The identification of FGR during pregnancy will contribute to the reduction of both perinatal morbidity and perinatal mortality. Aim. Based on a retrospective analysis, assess the obstetric and perinatal consequences of childbirth in women with antenatally undiagnosed fetal growth restriction. Materials and methods. An analysis of 488 cases of childbirth in women with singleton pregnancy, who gave birth to a live child, was conducted. In all cases, the gestational age was ≥22 weeks with a fetal weight less than the 10th percentile for the corresponding gestational age. Depending on the antenatally established diagnosis of FGR, two study groups were formed: group I consisted of 204 (41.8 %) cases with antenatally diagnosed FGR, group II – 284 (58.2 %) cases in which signs of FGR were identified after the birth of the child. Maternal characteristics, neonatal outcomes, and evaluation of short-term infant outcomes were analyzed. Results. Both groups were dominated by women with first births, the number of which was almost the same. Somatic pathology was almost 2 times more common in women of group I, 17.2 %, compared to 9.2 % of women in group II (p < 0.01), this indicates that the majority of women who were not diagnosed with FGR during pregnancy belong to the low-risk group. Fetuses with impaired blood flow in the umbilical cord arteries were twice as common in group I, 49.5 % versus 23.9 % in group II (p < 0.0001), and the frequency of absent/reversible end flow in the umbilical arteries in group I compared to group II, prevailed 3 times (p < 0.0001), indicating more serious lesions of the placenta and, as a result, early manifestation of the fetal condition disorder. The frequency of premature abdominal delivery was 3.75 times higher in group I compared to group II. The most frequent indication for cesarean delivery in both groups was signs of fetal distress syndrome. Analysis of neonatal outcomes showed that the average birth weight was significantly lower in group I and was 2180 ± 55 g against 2420 ± 61 g in group II (p < 0.0001). The need for hospitalization of newborns in the intensive care unit had no statistical difference between the groups (p > 0.05). However, the complications of the early neonatal period and the total length of stay in the hospital were greater in children of the I group, compared to the II group (p < 0.0001). Conclusions. The results of the conducted research indicate a low level of prenatal diagnosis of fetal growth restriction. Most pregnant women with antenatally undiagnosed fetal growth restriction belong to the group of low perinatal risk. The most frequent indication for cesarean section operation, regardless of the date of delivery, in both groups were signs of fetal distress, the frequency of which was 1.5 times higher in the antenatally diagnosed fetal growth retardation group. Newborns with an undetected growth anomaly before delivery have an increased risk of fetal distress, the severity of which is determined by the degree of deterioration of fetal oxygenation, and not by weight percentile, which requires more careful observation of fetuses with signs of growth restriction.